2013
DOI: 10.1186/1471-2148-13-42
|View full text |Cite
|
Sign up to set email alerts
|

Genome differentiation in a species pair of coregonine fishes: an extremely rapid speciation driven by stress-activated retrotransposons mediating extensive ribosomal DNA multiplications

Abstract: BackgroundSympatric species pairs are particularly common in freshwater fishes associated with postglacial lakes in northern temperate environments. The nature of divergences between co-occurring sympatric species, factors contributing to reproductive isolation and modes of genome evolution is a much debated topic in evolutionary biology addressed by various experimental tools. To the best of our knowledge, nobody approached this field using molecular cytogenetics. We examined chromosomes and genomes of one po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 58 publications
2
113
1
Order By: Relevance
“…However, karyotyping suggests that this is not the case, at least at the whole-chromosome scale as both karyotypes are essentially the same ( figure 1a,b). Yet, our results cannot rule out the possibility that more subtle changes at the [44]. Alternatively, nucleotide divergence among ecotypes may prevent the proper functioning of DNA repair pathways, such as the highly conserved MMR DNA repair pathway [45], and result in meiotic breakdown.…”
Section: (A) Potential Mechanisms Underlying Chromosome Segregation Bmentioning
confidence: 56%
“…However, karyotyping suggests that this is not the case, at least at the whole-chromosome scale as both karyotypes are essentially the same ( figure 1a,b). Yet, our results cannot rule out the possibility that more subtle changes at the [44]. Alternatively, nucleotide divergence among ecotypes may prevent the proper functioning of DNA repair pathways, such as the highly conserved MMR DNA repair pathway [45], and result in meiotic breakdown.…”
Section: (A) Potential Mechanisms Underlying Chromosome Segregation Bmentioning
confidence: 56%
“…Additionally, the absence and presence of Mutsu retrotransposon RNA and piRNA in eggs, respectively, together with the reversed situation in adult tissue, fuel the need to investigate the obvious link between 5S rRNA and these sequence-specific non-LTR retrotransposons. All of this sparks the notion that the retrotransposon elements are involved in the way the copy numbers evolved in both maternal-and somatic-type 5S rDNA loci (Rebordinos et al 2013), similar to that reported in 45S (Symonová et al 2013).…”
Section: Resultsmentioning
confidence: 84%
“…1) suggests additional chromosomal pairs bearing 45S rDNA (Oliveira et al, 1993), consistent with the occurrence of rearranged karyotypes. Chromosomal rearrangements, such as inversions, translocations, and transposon-mediated transpositions (Symonová et al, 2013), could explain the diversification of the major rDNA clusters in Corydoras.…”
Section: Discussionmentioning
confidence: 99%
“…paleatus (Upper Iguaçu and Upper Ribeira rivers) and in C. lacrimostigmata, 5S and 18S rDNA sequences were found to be non-syntenic and on different chromosomes, giving rise to heterokaryotypes due to chromosome rearrangements, such as translocations, inversions, and transpositions. According to Symonová et al (2013), there is evidence to suggest that ribosomal DNA spreading is involved in chromosome rearrangements, thereby affecting recombination rates in both genomes and ultimately leading to a rapid genome divergence. Thus, the detection of the rearranged rDNA chromosome sites is an important source of evidence for mechanisms that could prevent genetic introgression.…”
Section: Discussionmentioning
confidence: 99%